Surface modification of structural materials by low-energy high-current pulsed electron beam treatment; AIP Conference Proceedings; Vol. 1623 : International Conference on Physical Mesomechanics of Multilevel Systems 2014, Tomsk, Russia, 3–5 September 2014 - Panin A. V. Alexey Viktorovich; Kazachenok M. S.; Borodovitsina O. M. Oksana Mikhaylovna; Sinyakova E. A.; Ivanov Yu. F. Yuriy Fedorovich; Leontieva-Smirnova M. V. (2014, 2014)
Title screen